Improvement of the short- and long-term stability of high performance portable optically pumped cesium beam atomic clock - He, Xuan; Yuan, Zhichao; Chen, Jiayuan; Fang, Shengwei; Chen, Xuzong; Wang, Qing; Qi, Xianghui (Frontiers in Physics, 2022)
The research of optically pumped cesium beam atomic clock (OPCB) at Peking University has lasted for decades. At present, the short-term frequency stability is $3\times{10}^{-12}/\sqrt\tau$ and the long-term (5-day) frequency stability can reach $7\times{10}^{-15}$. The optimization methods of the short-term frequency stability are using laser induced beam spectrum to stabilize the laser frequency, using cyclic transition to detect the atomic state and using a cesium oven with a collimator to generate the cesium atomic beam. The methods of obtaining the good long-term frequency stability are controlling the microwave power based on the atomic transition probability, controlling the C-field intensity based on Zeeman frequency and controlling the laser power using fluorescence. The compact optically pumped cesium beam atomic clock of Peking University is expected to contribute to the field of timing, positioning, navigation and high speed digital communication.